Criteria for evaluation and selection of segments of the educational service. (Journal of Economic Research & Business Administration, 2015)
Segmentation of the market is an activity to identify potential groups of consumers of educational services of the university. The author presents the target market and the target segment of the educational institution.Identified three segmentation effects: profit maximization, the deceitfulness of values and ignore of the segment. Market segmentation of education can be done in three different ways: by consumer groups and the parameters of educational services; by competitors in the education market. There are used following basic criteria for evaluation and selection of market segments: quantitative parameters; availability of segment for the educational institution; significance of segments; profitability of the segment; compatibility of segment with the market of the main competitors; the efficiency of the work in selected market segment, taking into account the existing traditions of educational institution, its capacity and resources. Work on market segmentation is performed in order to select the best segment for him and the formation of a certain strategy. The author suggests the main factors of evaluation and selection of these market segments, which are implemented with the help of a set of procedures of portfolio analysis. The study touches all the key facilities of marketing studies, such as target groups of consumers, potential competitors, quality and choice of educational services, the promotion of these services in the market, pricing and own resources and potential of the company. The following levels of application of marketing are close to the universities: upper, middle, lower. Complex of marketing technologies (segmentation, positioning, internal and external marketing) takes into account the individual needs of consumers
Keywords: market segmentation; educational services; target market; target segment; marketing strategy; evaluation criteria; the effects of segmentation; profit maximization; the deceitfulness of dimension; ignored segment; competitors